2016
DOI: 10.7439/ijbar.v7i10.3659
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of hazardous effects of formaldehyde fumes on medical students

Abstract: Introduction: Formaldehyde is a naturally-occurring organic compound with the formula CH 2 O. The anatomists, technicians in biological science laboratories, and medical school students in dissection hall are regularly exposed to formaldehyde. My present study is investigates the relation between exposure to formaldehyde and acute changes in respiratory functions and non respiratory functions of 1 st year MBBS students. Material and Methods:The study was carried out on 150 1 st year medical students at L N Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…These are consistent with the results of other studies. 18 , 22 , 23 The decrease in Hgb and red blood cell count may be explained by the effect of metabolic end products and free radicals which shortened red blood cell lifespan. These free radicals can also alter erythrocyte membrane and heme protein synthesis in bone marrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are consistent with the results of other studies. 18 , 22 , 23 The decrease in Hgb and red blood cell count may be explained by the effect of metabolic end products and free radicals which shortened red blood cell lifespan. These free radicals can also alter erythrocyte membrane and heme protein synthesis in bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…These free radicals can also alter erythrocyte membrane and heme protein synthesis in bone marrow. 18 , 22 , 24 Moreover, the decline in these parameters might be due to the hematotoxic effect of benzene, which causes impairment of the hemopoietic system with bone marrow suppression leading to pancytopenia. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Similar symptoms were reported on medical students of different schools worldwide after exposure to formalin in anatomy dissecting rooms. The includes the students of the Dr. Vaishampayan Memorial Govt Medical College in India (Jain et al, 2012); the students of Himalayan Institute of Medical Sciences, Dehradun, India (Dhar and Chaudhuri, 2019); the students of Medical College, Raigarh in India (Kundu and Gangrade, 2015); the MBBS students in Srinagar, Jammu and Kashmir (Nisa et al, 2016) and in Bundelkhand, Sagar, India (Yadav and Yadav, 2014); the students of the Little Flower Institute of Medical Sciences and Research, Angamaly in India (Roy et al, 2015); the medical students at L N Medical College and Research center, Bhopal, India (Nair et al, 2016); the medical students at Niger Delta University, Nigeria (Onyije and Avwioro, 2012); the students of the College of Health Sciences, Nnamdi Azikiwe University in Nigeria (Chinedu et al, 2017;Ihim Augustine Chinedu et al, 2017;Chukwudi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Medical students, all through the dissection course, are exposed to formaldehyde whose exposure is considered to be one of the reasons of several chemical sensitivities (Nair et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This was in agreement with Abdullahi (2014) who showed that 95% of the respondents had no knowledge of the hazards and precautions to be taken against formaldehyde exposure as wearing protective equipment. Furthermore, unluckily, most of the students and laboratory assistants have slight or no knowledge about the carcinogenic effect of formaldehyde (Lang et al, 2008;Nair et al, 2016).…”
Section: Discussionmentioning
confidence: 99%